Low Thermal Conductivity through Dense Particle Packings with Optimum Disorder. Issue 14 (27th February 2018) - Nutz, Fabian A.; Philipp, Alexandra; Kopera, Bernd A. F.; Dulle, Martin; Retsch, Markus
Abstract: Heat transport plays a critical role in modern batteries, electrodes, and capacitors. This is caused by the ongoing miniaturization of such nanotechnological devices, which increases the local power density and hence temperature. Even worse, the introduction of heterostructures and interfaces is often accompanied by a reduction in thermal conductivity, which can ultimately lead to the failure of the entire device. Surprisingly, a fundamental understanding of the governing heat transport processes even in simple systems, such as binary particle mixtures is still missing. This contribution closes this gap and elucidates how strongly the polydispersity of a model particulate system influences the effective thermal conductivity across such a heterogeneous system. In a combined experimental and modeling approach, well‐defined mixtures of monodisperse particles with varying size ratios are investigated. The transition from order to disorder can reduce the effective thermal conductivity by as much as ≈50%. This is caused by an increase in the thermal transport path length and is governed by the number of interparticle contact points. These results are of general importance for many particulate and heterostructured materials and will help to conceive improved device layouts with more reliable heat dissipation or conservation properties in the future. Abstract : The thermal insulation capability of particulate materials can be strongly enhanced by the right degree of disorder. Using binary colloidal assemblies of two differently sized particles as a model platform, a reduction of ≈50% is obtained. This is caused by the elongation of the thermal transport path length, which is governed by the particle structure.